Pro-health action environmental water infants and young children - Joanna Harasimowicz (Kazimierz Wielki University, 2018)
Objectives: Recent years show a gradual decline in health activities and physical activity related to them. People located in a constant rush of civilization, increasingly do not see the need to spend time in an active way. This leads to a lowering of physical fitness among children and the consequences of this are developmental disorders, posture or being overweight. The aim of the study is to determine the effect of regular physical activity of children while swimming on their health. Material and methods: The study included 100 participants ranging in age from 3 months to 5 years. Children took part in swimming lessons regularly, at least once a week, for at least 6 months. Classes were held at the pool in Szczecin. In order to evaluate the health activities among participants, collected detailed information from parents children using a questionnaire consisting of 15 questions. The answers are summarized by adults. Results: Compiled results show that physical activity in an aqueous environment, a positive effect on the development of physical, mental, intellectual and social development among children and noticeable effect on their behavior. Test analysis revealed a statistical significant differences (p <0.001). It demonstrated that age, frequency and duration of the course have an impact on the obtained results. Conclusions: swimming classes support the normal development of motor, intellectual and social development among children, because health-promoting actions aimed at actively spending time in swimming pools, should be better promoted and financially more accessible for parents and their children